PET Imaging of Perceptual Learning-Induced Changes in the Aged Rodent Cholinergic System - Cisneros-Franco, J. Miguel; Voss, Patrice; Kang, Min Su; Thomas, Maryse E.; Côté, Jonathan; Ross, Karen; Gaudreau, Pierrette; Rudko, David A.; Rosa-Neto, Pedro; de-Villers-Sidani, Étienne (Frontiers in Neuroscience, 2020)
The cholinergic system functions as a gating mechanism that enhances attention and thus regulates adult neuroplasticity. Aging, however, is associated with a progressive degeneration of the cholinergic system that impairs the acquisition of skills acquired through learning or during functional recovery following neurological injury. Although cognitive training and perceptual learning have been shown to enhance auditory cortical processing, their specific impact on the cholinergic system remains unknown. Here we used [18F]-FEOBV, a positron-emission tomography (PET) radioligand that selectively binds to the vesicular acetylcholine transporter (VAChT), as a proxy to assess whether training on a perceptual task results in increased cholinergic neurotransmission. We show, for the first time, that perceptual learning is associated with region-specific changes in cholinergic neurotransmission detected by [18F]-FEOBV PET imaging, and corroborated with immunohistochemistry.